Taking law seriously: essays in honour of Peter Cane - Goudkamp, J (Hart Publishing, 2022)
This book celebrates the scholarship of Peter Cane. The significance and scale of his contributions to the discipline of law over the last half-century cannot be overstated. In an era of increasing specialisation, Cane stands out on account of the unusually broad scope of his interests, which extend to both private and public law in equal measure. This substantive breadth is combined with remarkable doctrinal, historical, comparative and theoretical depth. This book is written by admirers of Cane's work, and the essays probe a wide range of issues, especially in administrative law and tort law. Consistently with the international prominence that Cane's research has enjoyed, the contributors are drawn from across the common law world. The volume will be of value to anyone who is interested in Cane's towering contributions to legal scholarship and administrative law and tort law more generally.